ICT use among members of village development and security committee in Malaysia. - Mohamed Shaffril, Hayrol Azril (2011)
Information and Communication Technology or ICT has been widely used all over the world as an effective mechanism for rural development. Admitting the importance of ICT, the Malaysia government has launched a number of ICT programs and projects for the purpose of encouraging and exposing rural community to the ICT usage. Projects such as Rural Internet Desa (PID), Rural Info Center (MID), National Broadband Initiative (NBI) and National Information Technology Agenda (NITA) for examples have been initiated to meet such purposes. Apart from the implementation of these programs and projects, do the rural community especially their leaders which are the Village Development and Security Committee (VDSC) use ICT? In response to this question, this study aims to 1) describe the level of ICT usage among VDSC members in Malaysia 2) compare the level of ICT usage by selected socio-demographic factors among VDSC members 3) describe the level of components of extended technology acceptance constructs among VDSC members and 4) ascertain the relationship between extended technology acceptance constructs and ICT usage This is a quantitative study where the data required were collected using a tested and developed questionnaire. Using stratified random sampling, a total of 240 respondents from four states (Kedah, Terengganu, Perak and Johor) were selected. The selected respondents were among VDSC members in the Village Vision Movement (VVM). For the purpose of analyses, SPSS was used where descriptive and inferential analyses were employed. Based on the descriptive analyses, it can be seen that VDSC members in Malaysia do have a moderate level of ICT usage. Inferential analyses such as independent t-test and ANOVA have proved that the factors of ICT course attended, position in VDSC, level of education and job category do have significant differences with ICT usage. Based on the Pearson product moment correlation age was detected to have a significant and negative relationship with VDSC members’ ICT usage while income per month was detected to have a significant and positive relationship with VDSC members’ ICT usage. Further analysis done through Pearson product-moment correlation has concluded that all of the seven constructs studied have a positive and significant relationship with VDSC members’ ICT usage. Multiple Linear Regression through stepwise method employed proved that self-efficacy is the most significant contributor towards ICT usage.